#### Answer

$\dfrac{1}{y^2-1}$

#### Work Step by Step

$\dfrac{y^{-2}}{1-y^{-2}}=\dfrac{\dfrac{1}{y^2}}{1-\dfrac{1}{y^2}}=\dfrac{\dfrac{1}{y^2}}{\dfrac{y^2-1}{y^2}}=\dfrac{y^2}{y^2(y^2-1)}=\dfrac{1}{y^2-1}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\dfrac{1}{y^2-1}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.